Special education and sustainable development goals in Africa (2019)
In Africa, as in many continents of the world, education as one of the social institutions has been a subject of constant debate and discussion among stakeholders. It has continued to attract the attention of everybody and its importance to any nation in the world cannot be overemphasized. Special education which is an aspect of education has always been viewed as a tool for sustainable development in Africa. For this reason, this paper examined special education and sustainable development goals in Africa. Special education is the education of special needs person who have some forms of disabilities that are capable of frustrating them in benefitting fully from the regular physical education programme meant for those children without disabilities. Individual with special needs include those with one or more of the following: learning disabilities, mental retardation, emotional disturbance, auditory impairment, speech impairment, orthopeadic and visual impairment. In this paper, it was stressed that in spite of the limitations identified with such special needs persons, they still possess the ability to acquire education, and this will go a long way in making them globally useful and give them a better chance to contribute their own quota to the growth of Africa's economy. This paper further discussed the fact that for special education to continue to be a tool for reaching sustainable development goal in Africa it has to be repositioned. Finally, it must be noted that disability is referenced in various parts of the Sustainable Development Goals (SDGs) and specifically in parts related to education, growth and development, inequality, accessibility of human settlements, as well as data collection and monitoring of the Sustainable Development Goals. It is recommended that as persons with special needs are increasing in our society education should be made accessible to them so that they can give back to the society their own contributions for sustainable development. It is also recommended that persons with special needs should be involved in making decisions on issues that concern them.